Development of contextual mathematics teaching materials to facilitate students' problem-solving skills on systems of linear equations - Ananda, Yovita Dwi; Maimunah; Solfitri, Titi (Jurnal Absis: Jurnal Pendidikan Matematika dan Matematika, 2024)
The underlying issue in this research is the suboptimal level of students' mathematical problem-solving abilities. This study aims to develop contextual mathematics teaching materials on the topic of systems of linear equations in two variables to enhance students' problem-solving skills, meeting criteria for validity and practicality. The research employs the ADDIE model, encompassing the phases of analysis, design, development, implementation, and evaluation. The participants in this study consisted of 31 students from SMPN 8 Pekanbaru, including 6 students from class VIII.9 for the small group trial and 25 students from class VIII.2 for the large group trial. Data collection instruments included validation sheets and student response questionnaires. The findings indicated that the material expert validation score was 87.2% and the media expert validation score was 88.7%, both categorized as very valid. Furthermore, the practicality scores were 93% for the small group trial and 85.3% for the large group trial, both classified as very practical. Thus, it can be concluded that the developed teaching materials are both valid and practical for facilitating students' problem-solving abilities.